2019
DOI: 10.3389/fpls.2019.01224
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomics Yields New Insight Into Relationships Within Vernonieae (Asteraceae)

Abstract: Asteraceae, or the sunflower family, is the largest family of flowering plants and is usually considered difficult to work with, not only due to its size, but also because of the abundant cases of polyploidy and ancient whole-genome duplications. Traditional molecular systematics studies were often impaired by the low levels of variation found in chloroplast markers and the high paralogy of traditional nuclear markers like ITS. Next-generation sequencing and novel phylogenomics methods, such as target capture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 47 publications
0
32
2
Order By: Relevance
“…In addition, the conservative pipeline phyluce (Faircloth, 2016) is regularly employed for these markers, because it minimizes paralogy by removing a locus from the data set for a taxon if two or more contigs from that taxon match a targeted locus. This phylogenomic approach has been extensively tested for the Asteraceae and has yielded excellent phylogenetic accuracy and resolution at different taxonomic levels (Mandel et al, 2014, 2015, 2017, 2019; Herrando‐Moraira et al, 2018, 2019; Jones et al, 2019; Siniscalchi et al, 2019; Lichter‐Marck et al, 2020; Thapa et al, 2020). Nonetheless, we recognize that conflicting support may result for some lineages due to noisy data caused by paralogy of nuclear markers in a polyploid background in the family and in these tribes specifically.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the conservative pipeline phyluce (Faircloth, 2016) is regularly employed for these markers, because it minimizes paralogy by removing a locus from the data set for a taxon if two or more contigs from that taxon match a targeted locus. This phylogenomic approach has been extensively tested for the Asteraceae and has yielded excellent phylogenetic accuracy and resolution at different taxonomic levels (Mandel et al, 2014, 2015, 2017, 2019; Herrando‐Moraira et al, 2018, 2019; Jones et al, 2019; Siniscalchi et al, 2019; Lichter‐Marck et al, 2020; Thapa et al, 2020). Nonetheless, we recognize that conflicting support may result for some lineages due to noisy data caused by paralogy of nuclear markers in a polyploid background in the family and in these tribes specifically.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the limitations of our study, with a low number of individuals per species, we found that most of our newly described loci are polymorphic, although with relatively low number of alleles (Table 5). Given how readily the nuclear and plastid markers were successfully amplified and genotyped across three species, even with the considerable phylogenetic distance among them (Siniscalchi et al 2019b), our results show that the use of comparative genomic data for the development of microsatellite markers is promising. Complementary studies focusing on genetic diversity and structure of the three species presented here and other related taxa are being developed in order to elucidate the microevolutionary processes that drive diversification in these taxa and possibly in other endemic taxa from the Caatinga.…”
Section: Resultsmentioning
confidence: 95%
“…Although these seven species share many morphological similarities and environmental preferences, they do not form a monophyletic group, with C. martii actually being the sister taxa to the rest of the genus. The other six Caatinga species form a clade which is further subdivided into two clades (Siniscalchi et al 2019b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, most phylogenomic studies conducted on Compositae have succesfully employed the Hyb‐Seq technique based on 1061 COS loci, at family (Mandel & al., 2014, 2015, 2017, 2019; Jones & al., 2019), tribe (Herrando‐Moraira & al., 2019; Siniscalchi & al., 2019), and genus level (Herrando‐Moraira & al., 2018; Thapa & al., 2019). For Saussureinae, this method also allowed to recover a well‐supported phylogeny.…”
Section: Discussionmentioning
confidence: 99%